Implementasi Peraturan Bupati Bangli Nomor 66 Tahun 2022 Tentang Penyesuian Tarif Air Minum Pada Perumda Tirta Danu Arta - Luh Putu Astini Citra Dewi Manik; I Dewa Ketut Suryawan; Victorius Adventius Hamel (Policy and Maritime Review, 2024)
The Bangli Regency Government, through Perumda Tirta Danu Arta, manages water resources and implements Regency Regulation No. 66 of 2022 concerning Adjustments to Drinking Water Tariffs to improve clean water services and access. However, even though it has only been in effect for a year, this policy has led to complaints from the community regarding tariffs that are considered expensive and late payment penalties. This study aims to examine the implementation of this policy using qualitative methods and George C. Edward III's policy implementation theory (communication, resources, disposition, and bureaucratic structure). The results indicate that communication between Perumda and the community has not been effective, the budget is sufficient but there are no special funds for human resource training, Perumda only acts as a policy implementer without authority over tariffs, and a good organizational structure does not guarantee the success of policy implementation.